Causal relationship between immune cells and acute myeloid leukemia: a two-sample Mendelian randomization study - Fanhua Yu; Hao Jiang; Yena Gu (Discover Oncology)
Abstract Background Immune cells are crucial in the etiology of acute myeloid leukemia (AML). Given the genetic, epigenetic, and clonal complexities of AML, pinpointing factors linked to immunotherapy presents a formidable challenge. Moreover, investigations into the connection between immune cells and AML are still in their infancy, necessitating further studies to decode the intricate connections involved. Materials and methods Based on Mendelian independent distribution law, Mendelian randomisation (MR) is an analytical method mainly used in epidemiological aetiology inference. This bidirectional two-sample MR study aims to investigate the causal link between immune cell phenotypes and AML. Pooled phenotypic data from 3,757 individuals in a Sardinian cohort, encompassing 731 immune cell phenotypes, were utilized. Aggregate data on AML were sourced from the FinnGen project of the Finnish Biobank. We analyzed the sensitivity of the results and evaluated heterogeneity, employing Cochran’s Q test in conjunction with MR-Egger and MR-Presso to assess pleiotropy levels. Results 26 distinct immune cell types were identified that potentially linked causally with AML. Furthermore, our analysis indicated a bidirectional causal link between Resting Treg % CD4 Treg, BAFF-R on memory B cells and AML. Conclusion This investigation delineates the causal link between immune cell phenotypes and the pathogenesis of AML, thereby unveiling potential therapeutic avenues to modulate immune cell functions in AML patients. It aims to discover innovative therapeutic strategies that target immune evasion tactics to reinstate immune responses against leukemia.